Investigation of the energy efficiency of the military museum building by infrared thermography - Ristić, Slavica S.; Polić-Radovanović, Suzana R.; Jegdić, Bore V. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Infrared (IR) thermography, as a diagnostic technique, is used to find anomalies in the thermal signature of the Military museum building in Belgrade, to identify irregularities or deficiencies, such as wet materials, voids, or missing insulation and to inspect energy efficiency of the museum building and microclimatic indoor conditions.  It is very important to perform preventative maintenance and stop undesirable environment influences that induce structural damage, modification of materials and agglomeration of pollutants and microorganisms on the cultural heritage artifacts, stored in the museum depot or exhibited in the galleries. The main causes for corrosion in historical buildings and museum artifacts are moisture and changeable temperature conditions. This paper deals with the results obtained in the application of IR thermography in determination of these conditions in the Military museum building, where very important metal artifacts are exhibited and deposed. The results show poor thermal insulation, wet walls and, generally, low energy efficiency.
Keywords: thermography; wetting; museums; Military; insulator; energy efficiency of; buildings; artifacts